2003
DOI: 10.1017/s1049023x00000753
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Universal Medical and Public Health Definition of Terrorism

Abstract: The lack of a universally applicable definition of terrorism has confounded the understanding of terrorism since the term was first coined in 18th Century France. Although a myriad of definitions of terrorism have been advanced over the years, virtually all of these definitions have been crisis-centered, frequently reflecting the political perspectives of those who seek to define it.In this article, we deconstruct these previously used definitions of terrorism in order to reconstruct a definition of terrorism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…We limited our search to studies defined closely by time and place and excluded studies of torture, political repression, the effects of expatriation on political refugees, incidents of non-politically motivated violence such as criminal Terrorism substance use meta-analysis 895 shootings and studies of potential threats, such as bioterrorist attacks, rather than actual incidents. We defined substance use and misuse to include alcohol, cigarette, narcotics and prescription drugs, and terrorism as 'The intentional use of violence-real or threatened-against one or more non-combatants and/or those services essential for or protective of their health, resulting in adverse health effects in those immediately affected and their community, ranging from a loss of well-being or security to injury, illness, or death' [25].…”
Section: Methodsmentioning
confidence: 99%
“…We limited our search to studies defined closely by time and place and excluded studies of torture, political repression, the effects of expatriation on political refugees, incidents of non-politically motivated violence such as criminal Terrorism substance use meta-analysis 895 shootings and studies of potential threats, such as bioterrorist attacks, rather than actual incidents. We defined substance use and misuse to include alcohol, cigarette, narcotics and prescription drugs, and terrorism as 'The intentional use of violence-real or threatened-against one or more non-combatants and/or those services essential for or protective of their health, resulting in adverse health effects in those immediately affected and their community, ranging from a loss of well-being or security to injury, illness, or death' [25].…”
Section: Methodsmentioning
confidence: 99%
“…Terrorism is defined as ''the intentional use of violence against one or more non-combatants and/or those services essential for or protective of their health, resulting in adverse health effects in those immediately affected and their community, ranging from a loss of well-being or security to injury, illness, or death'' [5]. The results of several revisions of the consequences of disasters have shown that terrorism may be associated with a greater risk of psychopathology than other disasters [6].…”
Section: Introductionmentioning
confidence: 99%
“…We recognise that definitions of terrorism are variable and contentious [12][13][14]. This study used the US State Department's definition for Ôinternational terrorism', which includes attacks that are probably better classified in other ways.…”
Section: Limitations With This Analysis and Data Setmentioning
confidence: 99%